EXPRESSION OF PEROXISOME-PROLIFERATOR ACTIVATED RECEPTORS- IN DIABETICS, OBESE AND NORMAL SUBJECTS - Afzal, Naeema; Hassan, Mukhtiar; Fatima, Sadia; Tariq, Sumbal; Qayum, Iftikhar (Journal of Ayub Medical College Abbottabad, 2016)
Background: Current research in type 2 diabetes mellitus focuses on the role of Peroxisome-Proliferator Activated Receptors (PPARs) in the pathogenesis of the Insulin Resistance Syndrome (IRS), which are pre-diabetic lesion and the hallmark of fully developed type 2 diabetes mellitus. This study aims at identifying the abnormal status of the PPAR-g in adipose tissues of type 2 diabetes mellitus patients, when compared with matched normal controls. Methods: This cross-sectional study was conducted in Ayub Medical College, Abbottabad, from 2012 to 2014. Sample included three equal groups of patients. Group-1 with diagnosed type 2 diabetes mellitus, aged 40-65 years, acting as the test group, Group-2 included non-diabetic obese, and Group-3 with normal subjects. Transcription Factor Assay for Peroxisome Proliferator Activated Receptor Gamma (gamma PPAR) was done on ELISA Technique from Nuclear Extract procured from Adipose Tissue of the subjects. Results: Mean age of enrolled participants was 48.93 SD±6.52.years. Patients ranged between ages of 40 years to 67 years. The mean values of PPAR in normal, obese and diabetic group were 1.72 SD±0.28, 1.282 SE±0.18 and 1.283 SE±0.18 respectively. The difference in mean values of PPAR was significant p<0.05. Conclusion: The levels of PPAR-g in patients with type 2 Diabetes Mellitus and Obese cases are significantly lower than normal controls.